Prınsıp Kerja Sama Grıce dalam Aktıvıtas Pembelajaran Guru Praktıkan Bahasa Indonesıa di SMAN 12 Pandeglang; Sebuah Tınjauan Pragmatık - Maulana, Nanang (Jurnal Artikula, 2021)
This research was carried out at SMAN 12 Pandeglang when students carried out practical field experience activities as practical teachers with the aim of knowing the use of Grice's cooperative principles in learning activities. The research method used in this research is descriptive qualitative with observation and interview data collection techniques. Data from observations and interviews were then reduced, presented and concluded. From the results of the analysis carried out, it can be described that there is the use of the Grice cooperation principle carried out by practicing teachers. The use of the principle of cooperation includes maxim of quality, maxim of quantity, maxim of relevance. The use of the principle of cooperation above is well done by practicing teachers in order to deliver subject matter so that it can be digested and understood optimally by students.